2020
DOI: 10.1016/j.jseint.2020.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Plating and cortical bone grafting of clavicular nonunions: clinical outcome and its relation to clavicular length restoration

Abstract: Background The goal of this study was to evaluate whether plating and cortical bone grafting of shortened clavicular nonunions would restore clavicular length and enable bone healing. The association between the clavicular length difference (CLD) between sides and long-term functional outcome was also explored. Methods For this retrospective 2-center study, patients who underwent plate fixation with cortical bone grafting of a clavicular nonunion were assessed after ≥2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Restoration of clavicle length is not thought to influence clinical outcome of non-union surgery. 29 Muscle wasting, loss of proprioception and joint stiffness would presumably recover with time but subtle muscle fatigue as found in Potter et al.’s series may still exist. 15 Given the prolonged period of discomfort prior to fixation, mental health and treatment dissatisfaction may influence the ultimate recovery as found in other upper limb surgeries.…”
Section: Discussionmentioning
confidence: 89%
“…Restoration of clavicle length is not thought to influence clinical outcome of non-union surgery. 29 Muscle wasting, loss of proprioception and joint stiffness would presumably recover with time but subtle muscle fatigue as found in Potter et al.’s series may still exist. 15 Given the prolonged period of discomfort prior to fixation, mental health and treatment dissatisfaction may influence the ultimate recovery as found in other upper limb surgeries.…”
Section: Discussionmentioning
confidence: 89%
“…In the subanalysis of single-plate (n = 853) 6,11-42 vs. intramedullary (n = 93) 40,43-47 fixation, 39 studies were included (Table V). Of the 14 studies not included, 5 studies reported aggregate outcomes from single and double plating, 5 from multiple fixations methods, 3 from external fixators, and 1 from tension band wiring.…”
Section: Resultsmentioning
confidence: 99%
“…In the subanalysis of the use of bone graft (n = 687) 6,12,13,15,16,19,22-25,30,32-42,44-52 vs. no bone graft (n = 224) 11,17,23,26,27,29,43,53-55 , 41 studies were included (Table VI). The bone graft subjects had significantly longer follow-up than the nonbone graft group (3 vs. 2 years, p < 0.0001), but there was no difference in age (42 vs. 43 years).…”
Section: Resultsmentioning
confidence: 99%
“…In approximately two-thirds of patients with clavicle non-union, surgery is performed due to persistent symptoms [ 59 ]. In addition, surgical treatment of clavicular fracture non-union has achieved excellent healing results, depending on the reported literature [ 31 , 32 , 33 , 36 ]. Our study achieved a healing rate of 71% in the surgical intervention group.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, symptomatic pseudarthrosis is primarily surgically treated. Convincing healing results can be achieved by applying different plate configurations and plate localizations, usually combined with bone grafts [ 31 , 32 , 33 , 34 ]. However, a decisive disadvantage is the invasive nature of the intervention in clavicle non-union revision surgery, which is associated with all common complications of surgery.…”
Section: Introductionmentioning
confidence: 99%